UNDERSTANDING SALAFI THOUGHTS FROM DEBATES IN COMMUNITIES AND SOLUTIONS FOR THEIR SOLUTIONS - Hutagaluh, Oskar (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2023)
This study discusses the understanding of salafi religion and upheaval in the community so that there are conflicts in the community and find solutions in resolving these conflicts. Re-understanding the term salaf in classical literature, re-reading the historical development of